KEMAMPUAN SISWA MENGANALISIS UNSUR INTRINSIK DALAM CERITA LEGENDA “SI LANCANG” KELAS V GUGUS I HANG NADIM KECAMATAN TAMPAN KOTA PEKANBARU - Novita, Ririn Novita Ririn; Noviana, Eddy Noviana Eddy; Kurniaman, Otang Kurniaman Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Analyzing the intrinsic elements in the legend can be useful for elementary school children. In the curriculum of primary school students were told to look for elements that build up a work of literature that is character, disposition, setting, theme, viewpoint and mandate. But in primary school are still many students who have not been able to identify the intrinsic elements. This research was done to determine the student's ability to analyze the intrinsic elements of the legend "Si Lancang" Class V Gugus 1 Hang Nadim District of Tampan Pekanbaru conducted in three schools that is SDN 136 Pekanbaru, SDN 37 Pekanbaru, and SD IT Darul Hikmah. This research method is a survey research. The study population numbered 377 students and research samples as many as 77 students using a systematic sampling technique. Researchers get the data using instruments such as the legend "The Lancang" and problems of intrinsic element consisting of five elements, namely characters, characterizations, background, mandate, and themes. To analyze the data used technique scoring / grading is based on the assessment criteria which the maximum score is 4, and each value is grouped by categories of students' abilities. Results of the analysis of this study showed that the students' ability to analyze the intrinsic elements are in either category, that is 13 out of 77 students or 16.9%, both categories gained as many as 33 students or 42.8%, category is quite as many as 22 students or 28.6%. While students at less category as much as 9 students or 11.7%. Out of the five elements are the average student getting good value on the intrinsic elements of character and mandate that is the intrinsic elements of figures are 38 students who obtained the category of very good and 24 students in both categories, while the intrinsic elements of the mandate there are 31 students in the category of very good and 29 students in both categories. On characterizations intrinsic element more and more students are in the category of is quite as many as 26 students from the three schools. On the intrinsic elements of the background and theme of many students who have difficulty in analyzing it, particularly on the intrinsic elements background. It can be seen from the average obtained by the student in the background intrinsic element of 2.52 which is the average of the lowest and the theme of 2.6.Key words: Intrinsic Elements, Ability Students